An integrated model for international market entry location, entry timing and entry mode (ELETEM) decisions of Malaysian construction firms / Che Maznah Mat Isa - Mat Isa, Che Maznah (Institute of Graduate Studies, UiTM, 2016)
The strategy in making firms that are entering new foreign markets expand their businesses in terms of services, products, technology, human and other resources has been widely studied. However, a review of the literature suggests that a comprehensive model with existing theories to clearly guide the firms in adopting effective market entry decisions for construction firms is still lacking. Most previous studies have dealt with entry location (EL), entry timing (ET) and entry mode (EM) decisions in an isolated way by considering one dimension or a combination of dimensions in particular. Although there have been various studies relating to international market entry decisions, there is currently no model that attempts to integrate the common factors linked to ELETEM decisions for construction firms. The main aim of this study is to develop an integrated model by determining the mutually inclusive and significant factors (MISFs) that influence the ELETEM decisions. Questionnaires were administered to Malaysian construction firms with 62 managers participating in the survey. The findings on the proposed ELETEM decision model were then validated through interviews with 13 managers holding top managerial positions in the firms. It was found that majority of the firms have penetrated both ASEAN and non-ASEAN countries as late movers, using both equity (EQ) and non-equity (NEQ) modes in their international operations. Logistic regression predictive models for EL, ET and EM decisions were also established. The EL decision model predicts that firms need to acquire more knowledge related to the country factors in order to select suitable locations in both ASEAN and non-ASEAN regions…